Attendance to a “normal delivery” of choledocholithiasis - Cerezo-Ruiz, Antonio; Luque-Molina, Antonio; Giménez-Domenech, Rafael; Naranjo-Rodríguez, Antonio (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Cerezo-Ruiz A, Luque-Molina A, Giménez-Domenech R, Naranjo-Rodríguez A. Attendance to a “normal delivery” of choledocholithiasis. Turk J Gastroenterol 2019; 30(12): 1072-3.